Comparative analysis of lactate clearance as a predictor of postoperative complications in elderly patients with metabolic syndrome - A. A. Grazhdankin; P. I. Mironov; I. I. Lutfarakhmanov (Вестник анестезиологии и реаниматологии, 2025)
Introduction. The recently introduced cardiovascular-kidney-metabolic syndrome (CVKMS) is defined as a health disorder associated with obesity, diabetes mellitus, chronic kidney disease, and cardiovascular disease. Patients with CVKMS are at risk for postoperative complications. Postoperative hyperlactatemia is independently associated with an increased risk of death after major surgery.The objective was to conduct a comparative analysis of the dynamic parameters of blood lactate level with postoperative complications and duration of treatment of patients with metabolic syndrome (MetS) and CVKMS in non-cardiac surgical interventions.Materials and methods. 48 patients were divided into the CVKMS group (n = 16) and MetS group (n = 32). Both the peak concentration and clearance of blood serum lactate in the first 0, 6, 12, 18, 24 and 48 hours after surgery were calculated. Lactate concentration greater than 2.0 mmol/L was defined as hyperlactatemia. Endpoints were the severity of complications according to the Clavien–Dindo classification and the duration of postoperative treatment.Results. Peak lactate concentrations were statistically significantly higher and lactate clearance was significantly lower in the CVKMS group in comparison with MetS group. 54% of patients developed hyperlactatemia. Lactate clearance after surgery was significantly lower in patients with hyperlactatemia. In patients with CVKMS, the degree of severity of postoperative complications and the length of stay were significantly bigger.Conclusions. Elderly patients with CVKMS as compared to patients with MetS have a significantly higher blood lactate concentrations, more postoperative complications that require longer treatment. The identification of patients with CVKMS makes it possible to stratify the risks of postoperative complications.